Ammonia molecule and its applications in astrophysics - Polinovskyi, G.; Pavlenko, Ya.V.; Tennyson, J.; Yurchenko, S.N.; Barber, R.J. (Advances in Astronomy and Space Physics, 2012)
Recently a new ammonia line list BYTe was reported comprising more than 1.1 billion transitions and designed for temperatures up to 1500 K. In this study we present an application of this line list for modelling spectra of cool star. We generated oscillator strengths of NH3 using BYTe for a frequency range of 1–5 µm and applied it for computing synthetic spectra of cool carbon giants using the WITA program. A possibility of detection of ammoniain spectra of cool carbon giants is discussed.